2016
DOI: 10.1038/srep24736
|View full text |Cite
|
Sign up to set email alerts
|

Substantial dust loss of bioavailable phosphorus from agricultural soils

Abstract: Phosphorus (P) is an essential element in terrestrial ecosystems. Knowledge on the role of dust in the biogeochemical cycling of phosphorus is very limited with no quantitative information on aeolian (by wind) P fluxes from soils. The aim of this study is to focus on P cycling via dust emissions under common land-use practices in an arid environment by integration of sample analyses and aeolian experiments. The experiments indicate significant P fluxes by PM10 dust due to agricultural land use. Even in a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 42 publications
(54 reference statements)
1
34
0
Order By: Relevance
“…Yin and Chen, 2007;Karydis et al, 2017), but also through participating in biogeochemical cycles within terrestrial (e.g. Bielders et al, 2002;Katra et al, 2016). Jickells et al, 2005;Mahowald et al, 2018) upon deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin and Chen, 2007;Karydis et al, 2017), but also through participating in biogeochemical cycles within terrestrial (e.g. Bielders et al, 2002;Katra et al, 2016). Jickells et al, 2005;Mahowald et al, 2018) upon deposition.…”
Section: Introductionmentioning
confidence: 99%
“…At source, the loss of nutrients and fine particles due to dust emission may result in soil degradation (e.g. Bielders et al, 2002;Katra et al, 2016). Also, dust storms significantly affect regional air quality and human health (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were obtained also between conventional and organic agriculture, in which PM 10 emission was higher in Nirim (conventional crop field) compared with that in Migda (organic field). It was demonstrated that wind erosion and PM 10 emission from these soil lead to substantial loss of bioavailable phosphorus by dust, and possibly more essential nutrients, depending on land uses (Katra et al ., ). Following the results of wind‐erodible topsoil characteristics (Table ), differences in the potential of dust emission between the studied plots (Figure ) are expected.…”
Section: Resultsmentioning
confidence: 97%
“…Dust loading to the atmosphere from disturbed soils is particularly important because the chemical and biological compositions of which can be different from that of dust originating from natural desert sources (Hasselquist et al, 2011;Trujillo-González et al, 2016). Moreover, loss of microbial communities through wind erosion can reduce soil fertility and resistance to further erosion, introducing a notable feedback effect for rates of sediment loss (Acosta-Martinez et al, 2015;Borrelli et al, 2016;Colazo & Buschiazzo, 2015;Gao et al, 2016;Katra et al, 2016). Human exposure to dust particles can increase daily mortality, cardiovascular diseases and hospitalization rates (Perez et al, 2008;Yitshak-Sade et al, 2015;Vodonos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of recent experiments in semi-arid areas, following harvest and prior to cultivation, there seemed to be no statistically significant difference in soil loss between organic and conventional plots [95]. However, the research team also found that fields that had been cultivated using organic methods were often more susceptible to wind erosion than conventional plots, where no-till plowing or other practices left higher levels of vegetative cover [96].…”
Section: Desertification and Land Degradation Under Different Agriculmentioning
confidence: 98%